Humour Shifts in the Indonesian Dubbing of SpongeBob SquarePants Selected Episodes - Fikry Prastya Syahputra; Ely Hayati Nasution; Dea Yuanita Nasution (Talenta Publisher, 2026)
The purpose of this study is to analyse the types of humour shifts found in the Indonesian dubbing of the SpongeBob SquarePants cartoon. In this study, the author uses a descriptive qualitative method, drawing on data from 5 episodes of SpongeBob SquarePants. This study focuses on the translation of audiovisual theory. The findings of this study indicate that the translation of humour in audiovisual media is influenced by several factors, including linguistic differences, cultural references, and technical aspects such as timing and synchronization. In some cases, humour based on wordplay or phonetics cannot be produced directly in Indonesian, resulting in the loss of some humour analysis. However, the translation applies adaptive strategies to recreate the humour effect in the target language. Further analysis reveals that literal translation remains the dominant strategy in the Indonesian version. Thus, the translation of humour in the English-Indonesian dubbing of SpongeBob SquarePants involves various forms of translation shifts, as the translator balances linguistic constraints with the need to produce clear and contextual dialogue in the literary language.